Effects of Dietary American Cockroach Periplaneta americana Meal Inclusion on the Growth Performance, Antioxidant Capacity, and Immunity of Juvenile Rainbow Trout Oncorhynchus mykiss. (5th August 2022) - Long, Xiaowen; Liu, Yuting; Li, Yiqing; Li, Junjie; Zhao, Chengfa; Deng, Junming
Abstract : A feeding trial was conducted to assess the effects of dietary American cockroach Periplaneta americana meal (PAM) inclusion on the growth performance, antioxidant capacity, and immunity of juvenile rainbow trout Oncorhynchus mykiss. Five isonitrogenous and isolipidic diets were formulated to contain 100, 150, 200, 250, and 300 g/kg PAM (defined as PAM100-PAM300), respectively. The final body weight and weight gain rate of PAM250 were significantly higher than those of PAM100 and PAM150, and a higher specific growth rate was recorded in PAM200-PAM300. The highest levels of liver alanine aminotransferase and serum aspartate aminotransferase (AST) as well as serum total amino acids were detected in PAM150, while higher levels of liver AST and serum total protein were detected in PAM200-PAM300. The liver lipase activity of PAM150, PAM200, and PAM300 was significantly higher than that of PAM100. The liver glucose content in PAM150 was significantly higher than that in PAM250-PAM300. The highest liver catalase, alkaline phosphatase (AKP), and lysozyme activities were detected in PAM300; the lowest liver malondialdehyde content was detected in PAM250, while the highest serum total antioxidant capacity, catalase, and total superoxide dismutase activities were detected in PAM250. The highest serum AKP and acid phosphatase activities were detected in PAM150, while higher serum IgM and complement C3 contents were detected in PAM200-PAM300. In conclusion, dietary PAM inclusion at 200-300 g/kg could improve the growth performance, antioxidant capacity, and immunity of juvenile O. mykiss .